The realization of insulator-metal transition in a p-type metastable ZnSb by dual-phase nanostructure. (September 2020) - Wang, Guoxiang; Chen, Chen; Shi, Haizhou; Chen, Yimin; Shen, Xiang; Lotnyk, Andriy
Abstract : Insulator-metal transition (IMT) in a metastable phase of ZnSb-based films has been explored systematically. It is found that the reduction of thickness contributes to the precipitation of metastable structure and induces a wide controllable temperature span for the presence of metastable ZnSb phase, resulting in thickness dependent IMT of p-type ZnSb film during annealing process. The metastable structure can be obtained without any void generation after erbium-filling by the formation of crystalline/crystalline dual-phase nanostructure, which can improve the electrical transport and trigger IMT behavior with the temperature of 430 °C, providing a strategy for realizing multi-level data storage. Graphical abstract: Image, graphical abstract